MATH SOLVE

6 months ago

Q:
# Ms. Johnson asked her class to write anequivalent expression to14 − 9 + 21 − 7 + 2. Riley wrote the expression7(2 − 3 − 1) − 7 Ahmad wrote the expression7(2 − 3 − ) − 7 Ariana wrote the expression7(2 − 3 − ) − 7Who is correct? Explain how you know.

Accepted Solution

A:

Ahmad wrote the correct expression.To prove that 7(2d + 3k - dk) - 7 is equal to 14d - 9 + 21k - 7dk + 2Please check this solution:7(2d + 3k - dk) - 7 = 14d - 9 + 21k - 7dk + 27(2d + 3k - dk) - 7 = 14d + 21k - 7dk -9 + 27(2d + 3k - dk) - 7 = 14d + 21k - 7dk -7

Get the common variable which is 7.7(2d + 3k - dk) - 7 = 7(2d + 3k - dk) - 7

For checking, we can simplify the equation...from 7(2d + 3k - dk) - 7 = 14d - 9 + 21k - 7dk + 2We simplify it to:7(2d + 3k - dk) - 7 = 14d + 21k - 7dk -77 * 2d = 14d7 * 3k = 21k7 * - dk = -dk

Therefore, 7(2d + 3k - dk) - 7 is equal to 14d + 21k - 7dk -7

hope it helps

Get the common variable which is 7.7(2d + 3k - dk) - 7 = 7(2d + 3k - dk) - 7

For checking, we can simplify the equation...from 7(2d + 3k - dk) - 7 = 14d - 9 + 21k - 7dk + 2We simplify it to:7(2d + 3k - dk) - 7 = 14d + 21k - 7dk -77 * 2d = 14d7 * 3k = 21k7 * - dk = -dk

Therefore, 7(2d + 3k - dk) - 7 is equal to 14d + 21k - 7dk -7

hope it helps